Study guides

☆☆

Q: When x equals -3 then y equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

X+3=Y X=Y-3 X-Y=-3

y = -x + 3 y - 3 = -x -y + 3 = x Therefore x = 3 - y

If x+y = 3 and y times x = 2 then y = 1.

y=x y=6-x Set the two equations equal to each other to yield a solution: x=6-x 2x=6 x=3 x=3 will satisfy both equations, that is plugging in x=3 will give the same value for y y=(3)=3 y=6-(3)=3

y = 3x y = 3*19 = 57

Related questions

x=y

X+3=Y X=Y-3 X-Y=-3

x=4 y=x+3 y=4+3 y=7

3

y = -x + 3 y - 3 = -x -y + 3 = x Therefore x = 3 - y

6

(x, y) = (-3, -3) or (3, 3)

It is x = 2 and y = 1

y-x=3

x= z2 - 3

x - y = -3 -y = -x - 3 y = x + 3 y-int. = 3 x-int. = -3

x+y=3 y=3-2x so x+3-2x=3 so x=0 0+y=3 so y=3

People also asked